2010
DOI: 10.1155/2010/943516
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Effects ofInonotus obliquusin Colitis Induced by Dextran Sodium Sulfate

Abstract: A total of 28 male BALB/c mice (average weight 20.7 ± 1.6 g) were divided into 4 treatment groups and fed a commercial diet (A), a commercial diet + induced colitis by dextran sodium sulfate (DSS) (B), Inonotus obliquus (IO) administration (C), and IO administration + induced colitis by DSS (D). IO treatment (C, D) decreased the expression of tumor necrosis factor (TNF)-α and signal transducers and activators of transcription (STAT)1 compared to those of the colitis induced group (B). The expressions of IL-4 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 21 publications
1
23
0
Order By: Relevance
“…As a medical mushroom, Inonotus obliquus for containing myriad bioactive components known to exhibit potent effects of scavenging free radicals, antioxidant, hypoglycemic, antiviral, anti-inflammatory and antitumor, etc. (Chen et al, 2010;Choi et al, 2010;Shibnev et al, 2011), has become an important resource of developing nutraceutical and natural drugs for anticancer (Patel and Goyal, 2012). However, ecological harsh habitat & much slow growing speed derived limited natural resources and difficult artificial cultivation of I. obliquus to obtain fruiting body make it impossible to obtain large quantity of I. obliquus.…”
Section: Introductionmentioning
confidence: 99%
“…As a medical mushroom, Inonotus obliquus for containing myriad bioactive components known to exhibit potent effects of scavenging free radicals, antioxidant, hypoglycemic, antiviral, anti-inflammatory and antitumor, etc. (Chen et al, 2010;Choi et al, 2010;Shibnev et al, 2011), has become an important resource of developing nutraceutical and natural drugs for anticancer (Patel and Goyal, 2012). However, ecological harsh habitat & much slow growing speed derived limited natural resources and difficult artificial cultivation of I. obliquus to obtain fruiting body make it impossible to obtain large quantity of I. obliquus.…”
Section: Introductionmentioning
confidence: 99%
“…The manifestations of IBD include abdominal pain and cramps, weight loss, diarrhea, disrupted digestion, and rectal bleeding, accounting for substantial burden and discomfort in patients' everyday life. 2,3 Despite the fact that much efforts and resources have been invested into the investigation of IBD, the etiology and pathogenesis of the diseases remain elusive. Different groups of investigators have discovered that the p38 mitogen-activated protein kinase (MAPK) is a crucial mediator of inflammation in IBD.…”
mentioning
confidence: 99%
“…We found that IOE inhibited the secretion of NO, but not TNF-␣, in LPS-stimulated peritoneal macrophages ex vivo. Moreover, it was recently reported that extract from IO inhibited LPS-induced pro-inflammatory cytokines in vitro and exerted anti-inflammatory effects (Choi et al, 2010).…”
Section: Discussionmentioning
confidence: 99%